Post-mastectomy pain syndrome: mechanisms, prevention, and management strategies - Khadwardi, Faisal; Shaheen, Rakan; AlGarni, Ragad; Algumaei, Amgad; Alshaya, Deemah; Alfaraj, Fares; Hamdan, Mohamad; Alhariri, Mohammad; Wadi, Walaa; Alessa, Loulwa (International Journal Of Community Medicine And Public Health, 2026)
Post-mastectomy pain syndrome (PMPS) affects a significant proportion of breast cancer survivors and represents a challenging consequence of surgical treatment. It is primarily characterized by chronic neuropathic pain in the chest wall, axilla, or upper arm that persists beyond the expected healing period. The underlying mechanisms involve a combination of peripheral nerve injury, central sensitization, inflammatory processes, and maladaptive neuroplasticity. Surgical disruption of nerves such as the intercostobrachial and thoracodorsal plays a critical initiating role, while changes within the central nervous system sustain and amplify the pain experience over time. Preventive strategies span the entire surgical timeline. Preoperative psychological screening and education can reduce risk by addressing anxiety and pain sensitivity. Intraoperative nerve-sparing techniques and regional anesthesia such as paravertebral or pectoral nerve blocks help to blunt nociceptive signaling. Postoperative care focuses on controlling acute pain, early mobilization, and maintaining functions to limit the transition to chronic pain. Despite these interventions, a subset of patients continues to experience persistent symptoms that interfere with daily activities and quality of life. Therapeutic management is often multidisciplinary, incorporating pharmacologic agents like tricyclic antidepressants, serotonin-norepinephrine reuptake inhibitors, and gabapentinoids, along with physical therapy and psychological interventions. The variability in patient response remains a clinical hurdle. Newer approaches such as neuromodulation, ketamine infusions, and noninvasive brain stimulation are being explored for refractory cases. Persistent gaps in early identification, consistent treatment pathways, and personalized care models continue to limit progress. Addressing PMPS requires a comprehensive understanding of its biological and psychosocial components, along with strategies that evolve alongside advances in surgical and pain science. Effective care hinges on early intervention, tailored treatment, and improved integration across specialties involved in breast cancer recovery.